2021
DOI: 10.1158/1078-0432.ccr-21-2283
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-free Survival after Immune Checkpoint Inhibitor Therapy versus Targeted Therapy for Advanced Renal Cell Carcinoma: 42-Month Results of the CheckMate 214 Trial

Abstract: Purpose: Patients discontinuing immuno-oncology regimens may experience periods of disease control without need for ongoing anticancer therapy, but toxicity may persist. We describe treatment-free survival (TFS), with and without toxicity. Patients and Methods: Data were analyzed from the randomized phase III CheckMate 214 trial of nivolumab plus ipilimumab (n = 550) versus sunitinib (n = 546) for treatment-naïve, advanced re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…≧3 tended to be shorter than that of patients who did not experience an irAE of grade ≧3 (0.6 months and 6.1 months, respectively; 33 ). Several studies have shown that the discontinuation of treatment by the onset of irAEs was associated with a poor clinical outcome 34,35 .…”
Section: Discussionmentioning
confidence: 93%
“…≧3 tended to be shorter than that of patients who did not experience an irAE of grade ≧3 (0.6 months and 6.1 months, respectively; 33 ). Several studies have shown that the discontinuation of treatment by the onset of irAEs was associated with a poor clinical outcome 34,35 .…”
Section: Discussionmentioning
confidence: 93%
“… 40 Furthermore, treatment-free survival after the dual ICI combination was over twice that of sunitinib for intermediate/poor-risk (6.9 versus 3.1 months) and three times as long for favorable-risk patients (11.0 versus 3.7 months), suggesting that the ICI combination could allow for more treatment breaks. 50 However, acute immune-related AEs were observed that required careful monitoring and carry both the risk of treatment discontinuation and ongoing management for persistent complications. 30 Overall, however, the safety profile of the dual ICI combination was consistent with previous studies in RCC and other tumor types, 51 55 with dose delays, rapid diagnostic workups, appropriate timing, and the use of glucocorticoids (28.7% of patients received ⩾40 mg prednisone daily or equivalent) to manage any grade treatment-related select AEs.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment-free survival intervals are also important; when compared with patients who received sunitinib, patients who received ipilimumab-nivolumab had more breaks off of systemic therapy and more time without side effects. 21 …”
Section: Systemic Treatment Approach Of Patients With Mrcc In First-l...mentioning
confidence: 99%